A compact photomicroreactor design for kinetic studies of gas‐liquid photocatalytic transformations. Issue 7 (9th April 2015) - Su, Yuanhai; Hessel, Volker; Noël, Timothy
<x xml:space="preserve">Abstract</x> A compact photomicroreactor assembly consisting of a capillary microreactor and small‐scale light emitting diodes was developed for the study of reaction kinetics in the gas‐liquid photocatalytic oxidation of thiophenol to phenyl disulfide within Taylor flow. The importance of photons was convincingly shown by a suction phenomenon due to the fast consumption of oxygen. Mass transfer limitations were evaluated and an operational zone without mass transfer effects was chosen to study reaction kinetics. Effects of photocatalyst loading and light sources on the reaction performance were investigated. Reaction kinetic analysis was performed to obtain reaction orders with respect to both thiophenol and oxygen based on heterogeneous and homogeneous experimental results, respectively. The Hatta number further indicated elimination of mass transfer limitations. Reaction rate constants at different photocatalyst loadings and different photon flux were calculated. Furthermore, the advantages of this photomicroreactor assembly for studying gas‐liquid photocatalytic reaction kinetics were demonstrated as compared with batch reactors. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2215–2227, 2015